2022
DOI: 10.21608/znj.2022.296448
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Work Behavior and Its Relation to Knowledge Sharing among Nurses at Zagazig University Hospitals

Abstract: Background: Hospitals are a knowledge-based environment due to speedily changing medical technologies and demanding knowledge and skillful capital. So, it requires a skillful nurse who is active and can be receptive to new ideas. Thus, knowledge sharing plays a remarkable role in innovation that creates a change in new knowledge and innovative behavior. Aim of the study: was to investigate the relationship between knowledge sharing and innovative work behavior among nurses at Zagazig University Hospitals. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Furthermore, nurses may search to find better ways to do things, develop their experience and self-confidence at work, make better vital decisions, update and enrich resources with additional updates and information, and learn new techniques to improve patients care, all of these can't happen without sharing knowledge. This finding was in the same line with Elsiad et al, (2020) (25) who revealed that staff nurses had a high level of total knowledge sharing. In addition, Castaneda and Durán (2018) (26) who measured knowledge sharing behavior among participants and found workers had a high mean score of knowledge sharing behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, nurses may search to find better ways to do things, develop their experience and self-confidence at work, make better vital decisions, update and enrich resources with additional updates and information, and learn new techniques to improve patients care, all of these can't happen without sharing knowledge. This finding was in the same line with Elsiad et al, (2020) (25) who revealed that staff nurses had a high level of total knowledge sharing. In addition, Castaneda and Durán (2018) (26) who measured knowledge sharing behavior among participants and found workers had a high mean score of knowledge sharing behavior.…”
Section: Discussionsupporting
confidence: 90%